2013
DOI: 10.5812/nms.10661
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Hysterosalpingography and Laparoscopy for Tubal Patency in Infertile Women

Abstract: A B S T R A C TBackground: Tubal occlusion is one of the most frequent causes of infertility in women. The evaluation of the fallopian tube is necessary to determine the management plan for infertility. The two most important diagnostic procedures which are used for the evaluation of tubal patency are hysterosalpingography (HSG) and laparoscopy. Objectives: The aim of this study was to compare HSG and laparoscopic findings in the diagnosis of tubal patency. Patients and Methods:In a prospective study sixty two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 12 publications
3
36
1
2
Order By: Relevance
“…Hysterosalpingography can also be used to assess tubal patency, but it is associated with complications like infection, radiation exposure, contrast allergy, etc. 13 In present study, there was no complication reported in any procedure performed, except for mild postoperative pain in few patients.…”
mentioning
confidence: 68%
“…Hysterosalpingography can also be used to assess tubal patency, but it is associated with complications like infection, radiation exposure, contrast allergy, etc. 13 In present study, there was no complication reported in any procedure performed, except for mild postoperative pain in few patients.…”
mentioning
confidence: 68%
“…The average married life of a primary infertility patient was 4.6 ± 1.7 years and that of secondary infertility was 8.6 ± 2.3 years. In similar study conducted by Foroozanfard F et al 8 the average age in subjects of primary infertility was 26.25 years and in subjects of secondary infertility was 29.73 years. Mean duration of primary infertility was 5.79 ± 3.19 years and for secondary infertility was 5.97 ± 3.36 years.…”
Section: Age Distributionmentioning
confidence: 79%
“…In a similar study conducted by Foroozanfard et al 8 Laparoscopy showed bilateral tubal patency in 72.6% and unilateral or bilateral tubal patency in 27.40% (Table 6). In a similar study conducted by M Heis et al 10 found that 6.04% had bilateral tubal occlusion and 5.…”
Section: Tubal Factors Of Infertility On Laparoscopymentioning
confidence: 80%
See 1 more Smart Citation
“…A combination of several factors is found in approximately 20% of all couples worldwide. 3 Tubo-peritoneal factors are responsible for about 30-40% of cases of female infertility and hence evaluation of tubal patency represents a key step and a basic investigation in the assessment of infertile women. 4,5 Tubal occlusion is the most common underlying cause of infertility.…”
mentioning
confidence: 99%